OP09 An investigation of the clinical decision-making challenges experienced by ambulance clinicians during the management of patients presenting with COVID-19 symptoms. Issue 9 (19th August 2021) - Fitzpatrick, David; Ikegwuonu, Theresa; Duncan, Edward; Esposito, Martin; Moore, Matthew; Corfield, Alasdair; Best, Catherine; Andreis, Federico; Dobbie, Richard; Lowe, David
Abstract : Background: As well as patient impact, COVID-19 also considerably impacts on staff who have been required to make challenging patient care decisions in uncertain circumstances. This study investigated ambulance clinicians' experiences and use of decision support strategies during the COVID-19 pandemic. Methods: Forty-eight percent (16/33) of paramedics invited agreed to be interviewed. Telephone/video interviews were undertaken between September and December 2020. Framework analysis was undertaken. Data were indexed and charted by one researcher. A sample was then checked by two other researchers. Analytical interpretation was collectively undertaken by all three researchers to identify a higher-level conceptual understanding. Results: Four key themes were identified: Impact on clinical decision making – Deciding whether to take a patient to an Emergency Department is often challenging. Paramedics reported that COVID-19 increased the complexity of this process. Decision Support – Enhanced decision support was perceived as unequally available across the ambulance service. Where present, several paramedics reported that it was highly valuable. Use of Personal Protective Equipment (PPE ) – Routine use of extensive PPE was a very new experience for all participants. Some reported that the number of calls initially exceeded PPE availability. Personal impact of dealing with COVID-19 – Several paramedics stated that media reports combined with paramedics appearing in full PPE increased levels of anxiety among many patients they attended. Some participants were worried about catching COVID-19 and the possibility of taking the virus home to their families. Conclusions: Our findings suggest that COVID-19 has placed considerable stress on the ambulance service at both organisational and individual levels. These findings could inform implementation processes surrounding rapid clinical guideline development and communication. *This abstract was presented by Edward Duncan